Implementasi Metode Single Minute Exchange of Dies di Bagian Packing Dalam Upaya Meminimasi Pemborosan (Waste) Dan Peningkatan Produktivitas (Studi Kasus PT. SF) - Joko Hardono; Dian Friana Hidayat; Siti Halimatus Sa’diyah (Journal Industrial Manufacturing, 2024)
PT. SF is a company engaged in the pharmaceutical industry. This company has several problems faced, one of the problems that often occurs is the high time in the machine setup process , so that the fulfillment of production targets is disrupted. The number of types of products makes the number of model change processes which of course have different types, so that this has an impact on the amount of production produced. Therefore, this study was conducted to minimize setup time using the single minute exchange of dies (SMED) method. The results showed that there were 5 work stations in the packing section, where of these 5 work stations the one with the highest setup time was the cartoning machine workstation with an initial setup time of 63,84 minutes. After applying the single minute exchange of dies (SMED) method, the setup process can be lowered to 46,69 minutes. So it can save set-up time by 17.15 minutes. Keywords: SMED implementation, setup time improvement, internal setup, external setup